Analysis of Supplier Ability in Providing Raw Materials Cassava and Planning the Amount and Time of Arrival Raw Materials at PT. ABC - Yudi Daeng Polewangi (Budapest International Research and Critics University, 2020)
PT. ABC is a company engaged in the processing of cassava that produces tapioca flour. The smooth production of the company depends on the ability of suppliers to provide cassava raw materials. Problems that arise in the company are the frequent vacancies caused by the unavailability of raw materials and on other days there are high working hours due to the amount of raw materials received by the company exceeding production capacity per day by also considering the economic age of raw materials. Based on the research it was found that the ability of cassava processing companies based on production capacity amounted to 3,796 tons / month. In April 2019, total shipments of raw materials from suppliers amounted to 3,987 tons, which means it exceeded the company's capacity. But still visible emptiness of raw materials on certain days, this is due to lack of planning the arrival time of raw materials. Based on the analysis using forecasting methods, it is found that the amount of raw material provided is able to meet the production capacity each month but has not been able to meet customer demand. The steps that must be taken are determining the amount of raw materials that can be provided by the supplier, determining the amount of raw material usage, determining the amount and time of delivery of raw materials. Delivery of raw materials can be done 2 or 3 times per week with the amount of raw materials sent adjusted to the needs of the day the company.